Synergism of the pharmacological effect of glycine and thiotriazoline - I. F. Bielenichev; A. A. Yehorov (Zaporozhye State Medical University, 2021)
Aim. To establish the effect of the glycine and thiotriazoline (4:1) combination on the parameters of the energy production of the mitochondria of the rat brain under the conditions of simulating an acute cerebrovascular accident. Materials and methods. The experimental part was performed on 90 male Wistar rats weighing 180-200 g. To model acute cerebrovascular accident (ACVA) by ischemic type, a classical model was used, where common carotid arteries had been ligated bilaterally. All animals were divided into 5 experimental groups: the first - intact (sham-operated rats, which during anesthesia had their common carotid arteries separated without ligation); the second - rats with ACVA (control); the third - rats with ACVA, which underwent intragastric administration of glycine at a dose of 200 mg/kg in the form of a tablet mass every day for 4 days; the fourth - rats with stroke, which every day for 4 days underwent intragastric administration of a combination of glycine and thiotriazoline (4:1) in the form of a tablet mass; the fifth - rats with ACVA, which underwent every day intragastric administration of piracetam in the form of a tablet mass at a dose of 500 mg/kg. The sampling of biological material (brain) for research was carried out on the fourth day of the experiment according to the standard method. The mitochondrial fraction was isolated by differential centrifugation in a refrigerated centrifuge. The manifestations of mitochondrial dysfunction, have been spectrophotometrically studied according to the degree of opening of the mitochondrial pore (MP) and mitochondrial transmembrane potential (Ψ). The assessment of the intensity of oxidative stress was determined by the markers of protein oxidative modification - aldehydephenylhydrazone (APH) and ketonedinitrophenylhydrazone (KPH) - spectrophotometrically. The state of energy metabolism was determined by the level of the most significant intermediates - ATP, lactate, succinate and malate. Results. In the group of animals with ACVA modeling, we noted a decrease in the level of ATP in mitochondria by 1.55 times, an increase in lactate content by 1.1 times, a decrease in SDH activity by 3.8 times and a decrease in succinate concentration by 1.1 times relative to the corresponding data of intact groups. Administration of a combination of glycine and thiotriazoline to experimental animals on the fourth day of ACVA modeling led to a 1.9-fold decrease in the opening of the mitochondrial pore and an increase in the charge of the inner mitochondrial membrane by 1.2 times, an increase in ATP in the mitochondrial fraction by 1.1 times, an increase in SDH activity by 3 times, and the activity of NAD-MDH - by 3.7 times, against the background of a decrease in the level of APH by 76.6 % and KPH by 80.7 %, relative to the group of animals with modeling of stroke by ischemic type. Conclusions. Modeling of ACVA leads to the initiation of oxidative stress and the development of an imbalance of energy metabolism intermediates in the brain mitochondria of experimental animals. Administration of a combination of glycine and thiotriazoline leads to a decrease in oxidative damage to mitochondria, increases the production of ATP due to the activation of compensatory mitochondrial-cytosolic shunts, mainly in malate-aspartate and succinate oxidase. In terms of the degree of influence on the indicators of energy metabolism, the combination of glycine and thiotriazoline reliably exceeds the similar actions of glycine and the reference drug - piracetam.